2009
DOI: 10.1177/1049909109331883
|View full text |Cite
|
Sign up to set email alerts
|

Does Caregiver Knowledge Matter for Hospice Enrollment and Beyond? Pilot Study of Minority Hospice Patients

Abstract: We examined the level of hospice knowledge of caregivers of minority elderly hospice patients and determined how it influences the hospice enrollment decision and the decision on the use of hospice services after enrollment. Based on qualitative analysis of medical records and interviews with caregivers of minority elderly hospice patients who received personal care from paid caregivers (eg, other than family caregivers), we found that hospice knowledge increased access to hospice among minority patients who o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…For example, qualitative data suggest that increased knowledge about the benefits of hospice increases likelihood of hospice enrollment. 33 Furthermore, having a caregiver with strong religious beliefs is associated with lower likelihood of utilizing hospice services among Latinos and African Americans 34 while other studies find no association between caregiver characteristics and hospice use among those with dementia. 35 The aim of this study was to determine whether spousal health-related characteristics and educational attainment independently impact use of hospice among patients with serious illness.…”
Section: Introductionmentioning
confidence: 96%
“…For example, qualitative data suggest that increased knowledge about the benefits of hospice increases likelihood of hospice enrollment. 33 Furthermore, having a caregiver with strong religious beliefs is associated with lower likelihood of utilizing hospice services among Latinos and African Americans 34 while other studies find no association between caregiver characteristics and hospice use among those with dementia. 35 The aim of this study was to determine whether spousal health-related characteristics and educational attainment independently impact use of hospice among patients with serious illness.…”
Section: Introductionmentioning
confidence: 96%
“…However, to our knowledge, most studies on EOL care have focused on terminal (hospice or hospice eligible) patients 6,21,24,27 or their families/caregivers. 30,31 There are some studies that have focused on EOL knowledge and attitudes in younger populations, 18,32 but hardly any studies of EOL knowledge and attitudes have been conducted using large, ethnically diverse samples with large age ranges. 20,29 Moreover, studies that have investigated ethnocultural differences in EOL decisions have used very small sample sizes, making generalizability difficult.…”
Section: Introductionmentioning
confidence: 98%
“…Minority patient and caregiver knowledge is associated with willingness to engage in advance care planning and preference for comfort care over aggressive care at EOL (Chung, Essex, & Samson, 2009;Volandes, Ariza, Abbo, & Paasche-Orlow, 2008;Volandes, Barry, Chang, & Paasche-Orlow, 2010;Volandes et al, 2007;. In a study of Spanish-speaking Latino patients, Volandes, Ariza, et al (2008) found that after viewing a 2-minute video of an individual with advanced dementia, preference for comfort care nearly doubled and desire for life-prolonging care reduced from 40 to 8% of patients.…”
Section: Patient Knowledgementioning
confidence: 96%
“…Similarly, African Americans have demonstrated improved knowledge of hospice and greater intentions to enroll following review of a specialized educational brochure (Enguídanos, Kogan, Lorenz, & Taylor, 2011). Minority caregiver knowledge is also associated with enrollment in hospice earlier in the disease trajectory and more active caregiver involvement in monitoring the quality of hospice care (Chung et al, 2009). …”
Section: Patient Knowledgementioning
confidence: 96%